Complexos fosfínicos de Ru(II) e Ru(III) com fármacos anti-tuberculose e seus derivados - Cunha, Lucas Vinicius Pozzi da (Universidade Federal de São Carlos, 2012)
In this work were synthesized ruthenium complexes using pyrazinamide (PZA), a first-line drug in the treatment of tuberculosis, as well as isonicotinamide (ins) and isonicotinic acid (INA), isoniazid derivatives, as ligand. The reason why some drugs are been used as ligand is to enhance their activit or minimize the side effects. These mer-[RuCl3(dppb)(L)] (L = INA, PZA and ins) complexes was characterized by cyclic voltammetry, FTIR, UV-Vis, elemental analysis and conductivity. Electrochemical studies showed the presence of Ru (III) and other species, both binuclear and mononuclear that are generate in solution by a specific potential application, as described in the literature for mer-[RuCl3(dppb)(H2O)]. The assignment of the main absorption bands in FTIR spectra showed the appearance of metal-ligand bonds. The UV-Vis spectra showed three bands related to ligand charge transfer to the metal (LMCT), and the neutrality of these complexes was confirmed by conductivity. The series of complexes [RuCl(ins)(dppb)(N-N)]PF6 was characterized by NMR, cyclic and differential pulse voltammetry, FTIR, UV-Vis, X ray diffraction, elemental analysis and conductivity. The presence of two doublets in the NMR spectra showed that the phosphorus atoms are not equivalent. When the chloride ligand is exchanged by a N-heterocyclic ligand the redox potential was increased if compared with the precursor complex potential, due to the nature of the π-receptor ligand ins. The crystal structures of complexes [RuCl(ins)(dppb)(bipy)]PF6 and [RuCl(ins)(dppb)(phen)]PF6 were determined by X ray and were suggested that the ins ligand is in trans position to the phosphorus atom of dppb. The conductivity indicated the presence of an anion PF6, stabilizing the complexes. Anti-M. tuberculosis and cytotoxicity studies were performed for these complexes [RuCl(ins)(dppb)(N-N)]PF6 and mer-[RuCl3(dppb)(L)] and their respective free ligands.
Keywords: Química; Complexo de rutênio; Química bioinorgânica; CIENCIAS EXATAS E DA TERRA::QUIMICA